Dickens, the suspended quotation and the corpus - Mahlberg, Michaela; Smith, Catherine (SAGE Publications, 2012)
This article presents a computer-assisted approach to the study of character discourse in Dickens. It focuses on the concept of the ‘suspended quotation’ – the interruption of a character’s speech by at least five words of narrator text. After an outline of the concept of the suspended quotation as introduced by Lambert (1981), the article compares manually derived counts for suspensions in Dickens with automatically generated figures. This comparison shows how corpus methods can help to increase the scale at which the phenomenon is studied. It highlights that quantitative information for selected sections of a novel does not necessarily represent the patterns that are found across the whole text. The article also includes a qualitative analysis of suspensions. With the help of the new tool CLiC, it investigates interruptions of the speech of Mrs Sparsit in Hard Times and illustrates how suspensions can be useful places for the presentation of character information. CLiC is further used to find patterns of the word pause that provide insights into how suspensions contribute to the representation of pauses in character speech.